The Doctrine of Perfuming (vasana) in the Yogacarabhumisastra and the Theory of Seed (bija) in the Abhidharmakosabhasya - Gao, Mingyuan (Religions of South Asia, 2021)
This paper examines the use of the notion of vasana in each layer of the Yogacarabhumisastra and its possible relation with the notion of bija in Vasubandhu’s Abhidharmakosabhasya. Though the two terms are generally taken as synonyms, they are used differently in the two texts. The last section of the paper discusses from this perspective some of Robert Kritzer’s arguments that attempt to vindicate the influence of the Yogacarabhumisastra over the composition of the Abhidharmakosabhasya. The examination of the connotations of vasana in the Yogacarabhumisastra shows that Vasubandhu’s notion of bija in the Abhidharmakosabhasya is less likely to have been directly influenced by the Viniscayasamgrahani of the Yogacarabhumisastra. On the other hand, the positions of the early Darstantikas and Srilata mentioned in some Vaibhasika texts reveal stronger connections with Vasubandhu’s ‘Sautrantika’ views than the Yogacarabhumisastra.